PERBEDAAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA YANG DIAJAR DENGAN PEMBELAJARAN KOOPERATIF THINK PAIR SHARE (TPS) DAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) PADA PEMBELAJARAN MATEMATIKA DI MTs SWASTA UMAR BIN KHATTAB - Dayana Lafadilla Purba; Ella Andhany (State Islamic University of North Sumatra, 2018)
This study aims to determine whether there is a difference in the ability of students' mathematical creative thinking that is taught by cooperative learning Think Pair Share (TPS) and cooperative Student Teams Achievement Division (STAD) on math learning at Private MTs Umar Bin Khattab. This research is a quantitative research with experimental research approach. The population is a student of class VII of Private MTs Umar Bin Khattab of the academic year 2017/2018 consisting of 2 classes. Of the 2 classes taken entirely; VII-1 class of 29 students as experiment class A with Think Pair Share (TPS) and VII-2 cooperative learning as many as 30 students as experimental class B with Student Teams Achievement Division (STAD) learning, where the two classes are sampled in research. Data collection techniques are observation and description test. Before this test is established as a data collection tool, it is first tested in class VIII Private MTs Umar Bin Khattab to see the validity, reliability, difficulty and differentiation of the problem. Data analysis consists of two parts: descriptive analysis and inferential analysis. The average value of post experimental class A test result is 87,414 and the average value of post-test of experiment class B is 80,167 and the difference of post-test result value between experimental class A and B is 7,247. From result of data analysis post-test experiment class A obtained Lcount≤Ltable that is 0,096 ≤ 0,163, and data post-test experiment class B obtained Lcount≤Ltablethat is 0,148≤0,161. So the post-test data of both experimental classes is Normal distributed. From the homogeneity test of post-test data both samples are homogeneous, where C2count< C2table is 0.001 <3.841. After hypothesis testing using t-test found that tcount>ttable is 1.703> 1.676 then Ho is rejected and Ha accepted. Thus it can be concluded that there are differences in the ability of students' mathematical creative thinking that is taught by cooperative learning Think Pair Share (TPS) and Student Team Achievement Division (STAD) on math learning at Private MTs Umar Bin Khattab.